Contagious Yawning and the Frontal Lobe: An fMRI Study - Nahab, Fatta B. (2010)
We conducted a slow event-related fMRI experiment with naïve subjects’ passively viewing yawn and various other control videos along with correlative behavioral testing. Specifically associated with the viewing of the contagious yawn was an area of activation in the ventromedial prefrontal cortex. These findings suggest a role for the prefrontal cortex in the processing of contagious yawning, while demonstrating a unique automaticity in the processing of contagious motor programs which take place independently of mirror neuron networks.